Danske og Internationale tendenser: Idræt og Sundhed - Skovgaard, Thomas (Forum for Idræt, 2015)
In the last decades there has been increasing recognition that physical inactivity represents a major health problem. Attention has been directed towards making the population more physical active in everyday life. Strategies have focused on individual, social and environmental determinants of health enhancing physical activity. This article argues that policies on physical activity, on top of addressing individual lifestyle factors, must include a strong focus on and plans for intervention in the social and built environments that influence the ability and interest in being physical active.